Introducción de los vehículos eléctricos en el centro de Latacunga y su influencia en la demanda. - Caisa Araque, Mayra Alexandra (2018)
The following research work carries out an analysis about the influence that will take place after the introduction of electric vehicles in the electricity demand from Cocha substation electric # 3 and whose service area is the centre of Latacunga city. To make this possible, surveys to the population sample of electricity users who lived in the zone of study were applied, so as to know about the feasibility on the implementation of this technology and begin to change consumers’ preference between fuel vehicles and electric vehicles. Based on obtained information, viability of the introduction of electric vehicles will be determined. Certain parts of this study allow to understand higher connecting possibilities of distribution power supplies for electric vehicles in different schedule (basis, middle and peak) stated by ARCONEL and also be able to visualize new demand curve regarding power and energy. In case of massive overload from electric vehicles, results will allow the one in charge to take correcting and improvement actions such as modification and implementation boosting at Cotopaxi Electric Company (ELEPCO S.A.) to avoid altering capacity limits from electric power supplies. Through regulations (Pliego Tarifario 2018) submitted by ARCONEL, the cost of this technology at different consumption periods was determined. In such matter, charging of electric vehicles is proposed in the basis schedule due to low fee. This will first help to the battery lengthening of useful life in electric cars and flattening of the electric demand curve.